2016
DOI: 10.1377/hlthaff.2015.1112
|View full text |Cite
|
Sign up to set email alerts
|

Understanding An Informed Public’s Views On The Role Of Evidence In Making Health Care Decisions

Abstract: Policy makers and practitioners increasingly believe that medical evidence plays a critical role in improving care and health outcomes and lowering costs. However, public understanding of the role of evidence-based care may be different. Public deliberation is a process that convenes diverse citizens and has them learn about and consider ethical or values-based dilemmas and weigh alternative views. The Community Forum Deliberative Methods Demonstration project, sponsored by the Agency for Healthcare Research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Findings were based on a randomized design, involving a large sample of patients with heterogeneous cancer diagnoses, and observed effects were robust across the cognitive, emotional, and behavioral subscales of the preference measure (see Table 2) as well as sensitivity and subgroup analyses that accounted for demographic and health characteristics. Given the level of public misunderstanding about palliative care, apparently even limited information can shift preferences, which underscores the importance of communicating medical evidence to patients (Alston et al, 2012; Carman et al, 2016). This research has implications for future studies aimed at improving quality of life in cancer by increasing palliative care utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Findings were based on a randomized design, involving a large sample of patients with heterogeneous cancer diagnoses, and observed effects were robust across the cognitive, emotional, and behavioral subscales of the preference measure (see Table 2) as well as sensitivity and subgroup analyses that accounted for demographic and health characteristics. Given the level of public misunderstanding about palliative care, apparently even limited information can shift preferences, which underscores the importance of communicating medical evidence to patients (Alston et al, 2012; Carman et al, 2016). This research has implications for future studies aimed at improving quality of life in cancer by increasing palliative care utilization.…”
Section: Discussionmentioning
confidence: 99%
“…It is important that medical students practice communication skills as evidence shows that perceptions of good communication between patients and physicians improve patient satisfaction 38. In addition, patients want autonomy and a role in determination of their medical care; physicians need to be able to understand the goals and needs of patients 14,15…”
Section: Discussionmentioning
confidence: 99%
“…Using both qualitative (e.g., focus groups, structured interviews) and quantitative methodology (e.g., surveys), these studies have provided consistent evidence that patients lacked familiarity with the concept of evidence‐based practice and had negative impressions of underlying principles (Becker et al, ; Carman et al, ; Scheyett et al, ; Tanenbaum, ). For example, Carman et al () found that when making medical decisions, healthcare consumers defined evidence‐based medical care incorrectly and did not value medical research as much as their personal preferences or their doctor's opinions. Similarly, Becker et al () found that consumers of adolescent substance use treatment were unfamiliar with the concept of evidence‐based therapy and had concerns that the approach seemed inflexible.…”
mentioning
confidence: 99%
“…To date, the scarce research on knowledge of EBMHC and perceptions of underlying EMBHC principles has either focused specifically on medical care (Carman et al, 2016(Carman et al, , 2010 or on specific patient populations (e.g., individuals with serious mental illness or substance use disorders; Becker et al, 2016;Scheyett, McCarthy, & Rausch, 2006;Tanenbaum, 2008). Using both qualitative (e.g., focus groups, structured interviews) and quantitative methodology (e.g., surveys), these studies have provided consistent evidence that patients lacked familiarity with the concept of evidence-based practice and had negative impressions of underlying principles (Becker et al, 2016;Carman et al, 2010;Scheyett et al, 2006;Tanenbaum, 2008).…”
mentioning
confidence: 99%